2017
DOI: 10.1002/2017ms000940
|View full text |Cite
|
Sign up to set email alerts
|

Using the Weak‐Temperature Gradient Approximation to Evaluate Parameterizations: An Example of the Transition From Suppressed to Active Convection

Abstract: Two single‐column models are fully coupled via the weak‐temperature gradient approach. The coupled‐SCM is used to simulate the transition from suppressed to active convection under the influence of an interactive large‐scale circulation. The sensitivity of this transition to the value of mixing entrainment within the convective parameterization is explored. The results from these simulations are compared with those from equivalent simulations using coupled cloud‐resolving models. Coupled‐column simulations ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…Using a single column model (SCM) and CRM, Ramsay and Sobel (2011) and Wang and Sobel (2011) showed that precipitation rate increases over local warm SSTs and is determined by the temperature anomaly rather than by the mean SST. Daleu et al (2017) confirmed this result using two adjacent SCMs with different SSTs. The SST difference, if large enough, can suppress convection in the cold column and strengthen it in the warm column.…”
Section: Introductionsupporting
confidence: 71%
“…Using a single column model (SCM) and CRM, Ramsay and Sobel (2011) and Wang and Sobel (2011) showed that precipitation rate increases over local warm SSTs and is determined by the temperature anomaly rather than by the mean SST. Daleu et al (2017) confirmed this result using two adjacent SCMs with different SSTs. The SST difference, if large enough, can suppress convection in the cold column and strengthen it in the warm column.…”
Section: Introductionsupporting
confidence: 71%
“…For the dynamicist, the precision and controllability of CCPMs remains extremely valuable for inferring coupling mechanisms, despite some systematic shortcomings of the models (e.g., Varble et al 2014). Dynamically ''open'' protocols allow CCPM-simulated convection to be interrogated cleanly for responses to certain forcings while coupled to parameterized or simplified large-scale dynamics (e.g., Sobel and Bretherton 2000;Raymond and Zeng 2005;Herman and Raymond 2014;Raymond and Flores 2016;Daleu et al 2016) that are less chaotic than our tangent linear GCM's dynamics. Direct if rather method-dependent contacts could then be made with observations, at least ''to some degree'' (Wang et al 2013(Wang et al , 2016 or statistically (Sentić et al 2015), using idealized probing signals for sensitivity characterizations (Sessions et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that one major confounder (an important but unmeasured variable) shaping filter-scale Q variability in nature is filter-scale vertical velocity [w], which CCPMs (and therefore their causal response matrices M and G) lack for structural reasons. Advection of basic-state vertical gradients by a Qproportional [w] under the weak temperature gradient approximation could be incorporated as a linear effect in a modified matrix (Kuang 2012), or captured in other parameterized large-scale dynamics approaches (e.g., Daleu et al 2016Daleu et al , 2017, but here we shall instead utilize a more explicit mechanism for coupling CCPM sensitivities to larger-scale dynamics, in order to bring those sensitivities into an observation-comparable domain.…”
Section: Coupling With [W]: Toward An M-based Quantity More Comparable To Observationsmentioning
confidence: 99%
“…where u and q are potential temperature and specific humidity of water vapor, respectively, and the subscript ''LS'' denotes large scale. Note that, unlike the conventional WTG (e.g., Daleu et al 2017) this method does not require a special treatment in the well-mixed boundary layer (e.g., Sobel and Bretherton 2000), as vertical gradients vanish, because the shallow modes with small phase speed are weakly relaxed toward the target profile.…”
Section: B Parameterized Large-scale Dynamicsmentioning
confidence: 99%
“…The resulting large-scale vertical motion W then acts in a way to restore tropospheric temperature and maintain its horizontal homogeneity over large variations in surface forcings (e.g., Bretherton and Smolarkiewicz 1989). This mechanism of a two-way interaction between convection and large-scale motion has long been implemented in single-column models (e.g., Sobel and Bretherton 2000;Ramsay and Sobel 2011) as well as cloud-resolving models (e.g., Raymond and Zeng 2005;Wang and Sobel 2011;Romps 2012;Daleu et al;Anber et al 2014Anber et al , 2015a. Varying SST while strongly relaxing freetropospheric temperature toward a fixed profile can be thought of as varying the relative SST, or the difference between local and tropical mean conditions.…”
Section: Introductionmentioning
confidence: 99%